A catalyst for hydrogen chloride oxidation and preparation method thereof

By using a supported ruthenium-based catalyst, the problems of existing catalysts being high cost, unfriendly and unstable in the hydrogen chloride oxidation reaction are solved, and efficient, economical and environmentally friendly chlorine preparation is achieved.

CN115945207BActive Publication Date: 2025-03-28ZHEJIANG UNIV OF TECH +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211634615.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-19
Publication Date
2025-03-28
Estimated Expiration
2042-12-19

AI Technical Summary

Technical Problem

The existing catalysts have high costs, unfriendly environment, and high temperature instability in the hydrogen chloride oxidation reaction, which limits the industrialization process of chlorine preparation.

Method used

The supported ruthenium-based catalyst is used, and the support is aluminum nitride, silicon nitride-aluminum nitride composite or silicon dioxide-aluminum nitride composite. It is prepared by impregnation method and high-temperature calcination after drying. The mass ratio of ruthenium to the support is controlled to improve the activity and stability of the catalyst.

Benefits of technology

It has achieved a low-priced, environmentally friendly, high catalytic activity and high temperature stability catalyst, suitable for catalytic oxidation reaction of hydrogen chloride, and has enhanced the industrialization potential of chlorine preparation.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a catalyst for hydrogen chloride oxidation and a preparation method thereof. The catalyst for hydrogen chloride oxidation is a supported ruthenium-based catalyst, and the carrier of the supported ruthenium-based catalyst is aluminum nitride, silicon nitride-aluminum nitride composite material, silicon dioxide-aluminum nitride composite material or silicon dioxide-silicon nitride-aluminum nitride composite material; in the silicon nitride-aluminum nitride composite material, the mass ratio of aluminum nitride to silicon nitride is 9-7:1-3; in the silicon dioxide-aluminum nitride composite material, the mass ratio of aluminum nitride to silicon dioxide is 9-7:1-3; in the silicon dioxide-silicon nitride-aluminum nitride composite material, the mass ratio of aluminum nitride to silicon dioxide and silicon nitride is 6-8:1-3:1-3. The supported ruthenium-based catalyst provided by the present invention is low in price, simple to prepare, and environmentally friendly. It is applied to the catalytic oxidation reaction of hydrogen chloride, showing high catalytic activity and high temperature stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to a catalyst for hydrogen chloride oxidation reaction and a preparation method thereof. Background Art

[0002] Chlorine is an important basic chemical raw material, widely used in new materials industries such as polyurethane, silicone, epoxy resin, chlorinated rubber, chlorinated polymers, chlorinated hydrocarbons, new energy industries such as polysilicon manufacturing, disinfectants, detergents, food additives, cosmetic additives and other fine chemical industries, synthetic glycerin, chlorobenzene series, chloroacetic acid, benzyl chloride, and other pesticide and pharmaceutical industries, as well as in papermaking, textile, metallurgy, petrochemical and other industries.

[0003] In most chlorine-consuming industries, there are two serious constraints in the use of chlorine. For example, in the chlor-alkali industry, the power consumption for producing one ton of chlorine is extremely high, and the by-product hydrogen chloride or hydrochloric acid is difficult to dispose of. The oxidation of hydrogen chloride to produce chlorine is a good idea to solve these two problems. In terms of development in recent decades, catalytic oxidation is the most effective solution, especially catalytic oxidation via Deacon reaction, which has the greatest industrialization potential due to its simple operation and low equipment cost.

[0004] The Deacon reaction is a reaction in which hydrogen chloride is oxidized to chlorine in the presence of a catalyst. The type of catalyst directly affects the conversion rate of hydrogen chloride in the Deacon reaction. Currently, the catalysts used in the Deacon reaction mainly use metal elements such as chromium, copper and ruthenium.

[0005] Patent GB1046313 discloses a supported RuCl3 catalyst using silica gel, pumice and Al2O3 as carriers, but the catalyst is easily deactivated.

[0006] Patent US5908607A discloses a catalyst with RuO2 as the main component, but the catalytic activity of the catalyst will gradually decrease with the extension of the operating time, and it is also easy to be irreversibly poisoned and deactivated due to impurities in the hydrogen chloride raw material (such as sulfur, aromatics, etc.) and errors in the process operation.

[0007] Patent CN102239003A discloses a titanium dioxide or zirconium dioxide catalyst containing a cavity obtained by dissolving a silicate material with an alkaline solution, wherein ruthenium is located inside the cavity. The structure of the catalyst cavity can prevent the growth of the active component ruthenium particles, but the patent not only does not disclose the specific reaction performance of the catalyst, but also has the disadvantages that when the silicate is dissolved by a strong alkali during the preparation process of the catalyst, the titanium dioxide or zirconium dioxide layer is easily destroyed, the dissolved silicate is discarded, and waste liquid is generated, which increases the cost of the catalyst.

[0008] The document (Zhang Junjun, Progress in the Technology of Producing Chlorine by Catalytic Oxidation of Hydrogen Chloride, China Chlor-Alkali [J], 2013 (5): 6-10) points out that Sumitomo Chemical Co., Ltd. of Japan has disclosed a catalyst with RuO2 as the main component. The catalyst is supported by titanium oxide, zirconium oxide, aluminum oxide or zeolite, among which the catalytic efficiency is highest when rutile TiO2 is used as the carrier. The mass ratio of ruthenium to the carrier is 2% to 6%. A third component other than ruthenium can also be added, such as palladium, copper compounds, chromium compounds, vanadium compounds, rare earth compounds and alkali metal compounds. The reaction adopts a fixed bed reactor, the reaction temperature is 200 to 380°C, and the reaction pressure is 101.33 to 55066.5 kPa. The molar feed ratio of hydrogen chloride to oxygen is 0.05 to 1.25. In 20 to 1000 h -1 Under the space velocity condition, the conversion rate of hydrogen chloride can reach 95.9%, and the service life of the catalyst can exceed 16000h. The catalyst contains precious metal components, and the catalytic activity of the catalyst will gradually decrease with the extension of the operating time. It is also easy to be irreversibly poisoned and deactivated due to impurities in the hydrogen chloride raw material and errors in the process operation. The problems of the above catalysts have seriously hindered the industrialization process of hydrogen chloride conversion to chlorine.

[0009] In summary, for the chlorine-related industry, the catalytic oxidation of hydrogen chloride to produce chlorine is an important link in the industrial chain. In order to achieve large-scale industrialization of this process at a relatively low cost, it is necessary to improve the catalyst preparation method suitable for fixed bed reactors. Among them, the key challenge lies in developing a low-cost, environmentally friendly, high-temperature stable catalyst preparation method to meet the needs of long-term use in industrial production of fixed bed reactors. Summary of the invention

[0010] The object of the present invention is to provide a catalyst for hydrogen chloride oxidation which is low in price, environmentally friendly, highly active and stable at high temperature and a preparation method thereof.

[0011] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:

[0012] In a first aspect, the present invention provides a catalyst for hydrogen chloride oxidation, wherein the catalyst for hydrogen chloride oxidation is a supported ruthenium-based catalyst, and the carrier of the supported ruthenium-based catalyst is aluminum nitride, a silicon nitride-aluminum nitride composite material, a silicon dioxide-aluminum nitride composite material or a silicon dioxide-silicon nitride-aluminum nitride composite material; in the silicon nitride-aluminum nitride composite material, the mass ratio of aluminum nitride to silicon nitride is 9-7:1-3; in the silicon dioxide-aluminum nitride composite material, the mass ratio of aluminum nitride to silicon dioxide is 9-7:1-3; in the silicon dioxide-silicon nitride-aluminum nitride composite material, the mass ratio of aluminum nitride to silicon dioxide and silicon nitride is 6-8:1-3:1-3;

[0013] The catalyst is prepared by the following method: taking a ruthenium chloride aqueous solution and adding ethanol to dissolve it, then adding a carrier, fully stirring it on a stirrer for 3-10 hours, then putting it into an oven to dry it at 60-100°C for 6-12 hours, and after drying, putting it into a muffle furnace, heating it to 200-300°C at a heating rate of 5-10°C / min, and calcining it at this temperature for 10-20 hours to obtain a supported ruthenium-based catalyst.

[0014] Preferably, the mass ratio of ruthenium in ruthenium chloride to the carrier is controlled to be 0.5-5:100.

[0015] Preferably, the aluminum nitride is prepared by the following method: aluminum powder and NH4Cl are ground and mixed evenly so that the weight ratio of NH4Cl in the mixture is between 30% and 70%; the mixture of aluminum and NH4Cl is placed in an alumina boat, the alumina boat is placed in the center of the heating section of a tubular furnace reactor, nitrogen is supplied to the tubular furnace reactor at a flow rate of 5-10 mL / min, and it is heated to a calcination temperature at a rate of 5-15°C / min, the calcination temperature is between 500-1000°C, and calcined at the calcination temperature for 3-10 hours, and then cooled to room temperature to obtain an aluminum nitride carrier.

[0016] Preferably, the silicon nitride-aluminum nitride composite material, silicon dioxide-aluminum nitride composite material or silicon dioxide-silicon nitride-aluminum nitride composite material is prepared by the following method: Si3N4 and AlN, SiO2 and AlN or SiO2, Si3N4 and AlN are mixed in a certain proportion, loaded into a ball mill, and ball milled at 100-300 rpm for 10-20 hours using anhydrous ethanol as a medium; the obtained ball milled product is poured into a quartz boat, placed in the center of the heating reaction section of a tubular furnace, heated to 400-1000°C at a rate of 10-20°C / min in a nitrogen atmosphere with a flow rate of 5-15mL / min, sintered for 3-10 hours, and cooled to room temperature to obtain a silicon nitride-aluminum nitride composite material, a silicon dioxide-aluminum nitride composite material or a silicon dioxide-silicon nitride-aluminum nitride composite material.

[0017] In a second aspect, the present invention provides a method for preparing a catalyst for hydrogen chloride oxidation, the preparation method comprising the following steps:

[0018] 1) Prepare the carrier by the following method a or b:

[0019] Method a: Grind and mix aluminum powder and NH4Cl evenly, so that the weight ratio of NH4Cl in the mixture is between 30% and 70%; put the mixture of aluminum and NH4Cl in an alumina boat, place the alumina boat in the center of the heating section of a tubular furnace reactor, supply nitrogen at a flow rate of 5-10 mL / min to the tubular furnace reactor, heat it to a calcination temperature at a rate of 5-15°C / min, the calcination temperature is between 500-1000°C, and calcine at the calcination temperature for 3-10 hours, and then cool to room temperature to obtain an aluminum nitride carrier;

[0020] Method b: Grind and mix aluminum and NH4Cl evenly, so that the weight ratio of NH4Cl in the mixture is between 30% and 70%; put the mixture of aluminum and NH4Cl in an alumina boat, place the alumina boat in the center of the heating section of a tubular furnace reactor, supply nitrogen gas at a flow rate of 5-10mL / min to the tubular furnace reactor, heat it to a calcination temperature at a rate of 5-15℃ / min, the calcination temperature is between 500-1000℃, and calcine at the calcination temperature for 3-10 hours, then cool to room temperature to obtain AlN; Si3N4 and AlN, SiO2 and AlN or SiO2, Si3N4 and AlN are mixed in a certain proportion, respectively, and loaded into a ball milling jar, and anhydrous ethanol is used as a medium, and ball milled at 100-300 rpm for 10-20 hours; the obtained ball milling product is poured into a quartz boat, and placed in the center of a tube furnace heating reaction section, and heated to 400-1000° C. at a rate of 10-20° C. / min in a nitrogen atmosphere with a flow rate of 5-15 mL / min, and sintered for 3-10 hours, and then cooled to room temperature to obtain a silicon nitride-aluminum nitride composite material, a silicon dioxide-aluminum nitride composite material or a silicon dioxide-silicon nitride-aluminum nitride composite material carrier;

[0021] 2) Take ruthenium chloride aqueous solution and add ethanol to dissolve it, then add the carrier, stir it on a stirrer for 3-10 hours, then put it into an oven and dry it at 60-100°C for 6-12 hours, put it into a muffle furnace after drying, heat it to 200-300°C at a heating rate of 5-10°C / min, and calcine it at this temperature for 10-20 hours to obtain a supported ruthenium-based catalyst.

[0022] Preferably, in step 2), the mass ratio of ruthenium to carrier is 0.5-5:100.

[0023] Preferably, in step 2), the temperature is raised to 250° C. at a heating rate of 5° C. / min and calcined for 16 hours.

[0024] The invention provides application of the supported ruthenium-based catalyst in a catalytic oxidation reaction of hydrogen chloride.

[0025] Furthermore, the application is specifically as follows: in a fixed bed reactor, the catalyst for hydrogen chloride oxidation is loaded, a mixed gas of hydrogen chloride and oxygen is introduced, the reaction temperature is 200 to 350° C., and chlorine and water are generated by reaction.

[0026] Furthermore, the raw gas HCl / O2=1 / 0.5~4, and the reaction pressure is 0.1MPa.

[0027] Further, the mass space velocity (WHSV) is 20 to 1000 h -1 .

[0028] Compared with the prior art, the beneficial effects of the present invention are: the supported ruthenium-based catalyst provided by the present invention is low-priced, simple to prepare, and environmentally friendly, and when applied to the catalytic oxidation reaction of hydrogen chloride, it exhibits high catalytic activity and high-temperature stability. DETAILED DESCRIPTION

[0029] The present invention is described below with specific examples. It is necessary to point out that the embodiments are only used to further illustrate the present invention, but cannot be understood as limiting the scope of protection of the present invention, and the present invention is not limited thereto in any way. Those skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.

[0030] The purity of the aluminum powder used in the embodiment of the present invention is 99.9%, the purity of NH4Cl is 99.5%, the nitrogen is high-purity nitrogen, and the concentration of the ruthenium trichloride aqueous solution is 0.1 g / ml.

[0031] Example 1

[0032] 1) Weigh 7g aluminum powder and 3g NH4Cl into a mortar and grind them to mix thoroughly; the mixture is placed in an alumina boat and placed in the center of the heating section of a tubular furnace reactor. Nitrogen gas is supplied to the tubular furnace reactor at a flow rate of 10mL / min, and it is heated to 1000℃ at a rate of 15℃ / min and burned at this temperature for 4 hours. Then cool to room temperature to obtain an aluminum nitride carrier sample. The aluminum nitride prepared by this step method is also provided for use in Examples 2-6.

[0033] 2) Loading ruthenium by impregnation. Take 1 ml of ruthenium chloride solution and add 10 ml of anhydrous ethanol to dissolve it, then pour in 10 g of aluminum nitride carrier and stir it thoroughly on a stirrer for 6 hours. Then put it in an oven and dry it at 70°C for 12 hours. The dried catalyst is placed in a muffle furnace and calcined at 250°C (at a heating rate of 5°C / min) for 16 hours to obtain an aluminum nitride-loaded ruthenium catalyst.

[0034] 3) The obtained aluminum nitride-supported ruthenium catalyst was loaded into a fixed bed reactor, and a mixture of hydrogen chloride and oxygen was introduced, HCl / O2=1 / 1, the reaction pressure was 0.1 MPa, the reaction temperature was 350°C, and the mass space velocity was 20 h -1 Under the above conditions, the conversion rate is 99% after 50 hours of reaction; after 1000 hours of reaction, the conversion rate of hydrogen chloride can reach 97%.

[0035] Example 2

[0036] 1) Weigh 7g AlN and 3g Si3N4, mix them, put them into a ball mill, use anhydrous ethanol as the medium (the amount of anhydrous ethanol should be enough to cover the mixture), grind them at 250 rpm for 24 hours to obtain a Si3N4-AlN composite material. Pour the obtained composite material into a quartz boat, place it in the center of the heating reaction section of a tube furnace, heat it to 1000°C in a nitrogen atmosphere with a flow rate of 10mL / min, and calcine it for 3 hours. Obtain a Si3N4-AlN composite material carrier.

[0037] 2) Loading ruthenium by impregnation method. Take 1 ml of ruthenium chloride solution and add 10 ml of anhydrous ethanol to dissolve it, then pour 10 g of Si3N4-AlN carrier and stir it thoroughly on a stirrer for 6 hours. Then put it in an oven and dry it at 70°C for 12 hours. The dried catalyst is placed in a muffle furnace and heated to 250°C at a heating rate of 5°C / min and calcined for 16 hours to obtain a Si3N4-AlN-loaded ruthenium catalyst.

[0038] 3) The obtained Si3N4-AlN supported ruthenium catalyst was loaded into a fixed bed reactor, and a mixture of hydrogen chloride and oxygen was introduced, HCl / O2=1 / 1, the reaction pressure was 0.1MPa, the reaction temperature was 350°C, and the mass space velocity was 20h -1 Under the above conditions, the conversion rate is 99% after 50h of reaction; after 1000h of reaction, the conversion rate of hydrogen chloride can reach 98%.

[0039] Example 3

[0040] 1) Weigh 7g AlN and 3g SiO2, mix them, put them into a ball mill, use anhydrous ethanol as the medium (the amount of anhydrous ethanol should be enough to cover the mixture), grind them at 250 rpm for 24 hours to obtain a SiO2-AlN composite material. Pour the obtained composite material into a quartz boat, place it in the center of the heating reaction section of a tubular furnace, heat it to 1000°C in a nitrogen atmosphere with a flow rate of 10mL / min, and calcine it for 3 hours. A SiO2-AlN composite material carrier is obtained.

[0041] 2) Loading ruthenium by impregnation method. Take 1 ml of ruthenium chloride solution and add 10 ml of anhydrous ethanol to dissolve it, then pour 10 g of SiO2-AlN carrier and stir it thoroughly on a stirrer for 6 hours. Then put it in an oven and dry it at 70°C for 12 hours. The dried catalyst is placed in a muffle furnace and heated to 250°C at a heating rate of 5°C / min and calcined for 16 hours to obtain a catalyst for catalytic oxidation of hydrogen chloride to produce chlorine.

[0042] 3) The obtained SiO2-AlN supported ruthenium catalyst was loaded into a fixed bed reactor, and a mixture of hydrogen chloride and oxygen was introduced, HCl / O2=1 / 1, the reaction pressure was 0.1MPa, the reaction temperature was 350°C, and the mass space velocity was 20h -1 Under the above conditions, the conversion rate is 99% after 50 hours of reaction; after 1000 hours of reaction, the conversion rate of hydrogen chloride can reach 97%.

[0043] Example 4

[0044] 1) Weigh 6g AlN, 2g SiO2 and 2g Si3N4, mix them, put them into a ball mill, use anhydrous ethanol as the medium (the amount of anhydrous ethanol should be enough to cover the mixture), grind them at 250 rpm for 24 hours to obtain a Si3N4-SiO2-AlN composite material. Pour the obtained composite material into a quartz boat, place it in the center of the heating reaction section of a tubular furnace, heat it to 1000°C in a nitrogen atmosphere with a flow rate of 10mL / min, and calcine it for 3 hours. Obtain a Si3N4-SiO2-AlN composite material carrier.

[0045] 2) Loading ruthenium by impregnation method. Take 1 ml of ruthenium chloride solution and add 10 ml of anhydrous ethanol to dissolve it, then pour 10 g of Si3N4-SiO2-AlN carrier and stir it thoroughly on a stirrer for 6 hours. Then put it in an oven and dry it at 70°C for 12 hours. The dried catalyst is placed in a muffle furnace and heated to 250°C at a heating rate of 5°C / min and calcined for 16 hours to obtain a catalyst for catalytic oxidation of hydrogen chloride to produce chlorine.

[0046] 3) The obtained Si3N4-SiO2-AlN supported ruthenium catalyst was loaded into a fixed bed reactor, and a mixture of hydrogen chloride and oxygen was introduced, HCl / O2=1 / 1, the reaction pressure was 0.1MPa, the reaction temperature was 350°C, and the mass space velocity was 20h -1 Under the above conditions, the conversion rate is 99% after 50h of reaction; after 1000h of reaction, the conversion rate of hydrogen chloride can reach 98%.

[0047] Example 5

[0048] 1) Weigh 6g AlN, 1g SiO2 and 3g Si3N4, mix them, put them into a ball mill, use anhydrous ethanol as the medium (the amount of anhydrous ethanol should be enough to cover the mixture), grind them at 250 rpm for 24 hours to obtain a Si3N4-SiO2-AlN composite material. Pour the obtained composite material into a quartz boat, place it in the center of the heating reaction section of a tubular furnace, heat it to 1000°C in a nitrogen atmosphere, and calcine it for 3 hours. A Si3N4-SiO2-AlN composite material carrier is obtained.

[0049] 2) Load ruthenium by impregnation. Take 1 ml of ruthenium chloride solution and add 10 ml of anhydrous ethanol to dissolve it, then pour the Si3N4-SiO2-AlN carrier (10 g) and stir it thoroughly on a stirrer for 6 hours. Then put it in an oven and dry it at 70°C for 12 hours. The dried catalyst is placed in a muffle furnace and heated to 250°C at a heating rate of 5°C / min and calcined for 16 hours to obtain a catalyst for catalytic oxidation of hydrogen chloride to produce chlorine.

[0050] 3) The obtained Si3N4-SiO2-AlN supported ruthenium catalyst was loaded into a fixed bed reactor, and a mixture of hydrogen chloride and oxygen was introduced, HCl / O2=1 / 1, the reaction pressure was 0.1MPa, the reaction temperature was 350°C, and the mass space velocity was 20h -1 Under the above conditions, the conversion rate is 99% after 50h of reaction; after 1000h of reaction, the conversion rate of hydrogen chloride can reach 97%.

[0051] Example 6

[0052] 1) Weigh 6g AlN, 3g SiO2 and 1g Si3N4, mix them, put them into a ball mill, use anhydrous ethanol as the medium (the amount of anhydrous ethanol should be enough to cover the mixture), grind them at 250 rpm for 24 hours to obtain a Si3N4-SiO2-AlN composite material. Pour the obtained composite material into a quartz boat, place it in the center of the heating reaction section of a tubular furnace, heat it to 1000°C in a nitrogen atmosphere with a flow rate of 10mL / min, and calcine it for 3 hours. A Si3N4-SiO2-AlN composite material carrier is obtained.

[0053] 2) Load ruthenium by impregnation. Take 1 ml of ruthenium chloride solution and add 10 ml of anhydrous ethanol to dissolve it, then pour the Si3N4-SiO2-AlN carrier (10 g) and stir it thoroughly on a stirrer for 6 hours. Then put it in an oven and dry it at 70°C for 12 hours. The dried catalyst is placed in a muffle furnace and heated to 250°C at a heating rate of 5°C / min and calcined for 16 hours to obtain a catalyst for catalytic oxidation of hydrogen chloride to produce chlorine.

[0054] 3) The obtained Si3N4-SiO2-AlN supported ruthenium catalyst was loaded into a fixed bed reactor, and a mixture of hydrogen chloride and oxygen was introduced, HCl / O2=1 / 1, the reaction pressure was 0.1MPa, the reaction temperature was 350°C, and the mass space velocity was 20h -1 Under the above conditions, the conversion rate is 99% after 50h of reaction; after 1000h of reaction, the conversion rate of hydrogen chloride can reach 96%.

[0055] Comparative Example 1

[0056] 1) Weigh 7 g AlN and 3 g Si3N4 and grind them evenly in a mortar to obtain a Si3N4-AlN composite material carrier.

[0057] 2) Loading ruthenium by impregnation method. Take 1 ml of ruthenium chloride solution and add 10 ml of anhydrous ethanol to dissolve it, then pour 10 g of Si3N4-AlN carrier and stir it thoroughly on a stirrer for 6 hours. Then put it in an oven and dry it at 70°C for 12 hours. The dried catalyst is placed in a muffle furnace and heated to 250°C at a heating rate of 5°C / min and calcined for 16 hours to obtain a Si3N4-AlN-loaded ruthenium catalyst.

[0058] 3) The obtained Si3N4-AlN supported ruthenium catalyst was loaded into a fixed bed reactor, and a mixture of hydrogen chloride and oxygen was introduced, HCl / O2=1 / 1, the reaction pressure was 0.1MPa, the reaction temperature was 350°C, and the mass space velocity was 20h -1 Under the above conditions, the conversion rate was 76% after 50h of reaction; after 1000h of reaction, the conversion rate of hydrogen chloride was 63%.

[0059] Comparative Example 2

[0060] 1) Weigh 7 g AlN and 3 g SiO2 and grind them evenly in a mortar to obtain a SiO2-AlN composite material carrier.

[0061] 2) Loading ruthenium by impregnation method. Take 1 ml of ruthenium chloride solution and add 10 ml of anhydrous ethanol to dissolve it, then pour 10 g of SiO2-AlN carrier and stir it thoroughly on a stirrer for 6 hours. Then put it in an oven and dry it at 70°C for 12 hours. The dried catalyst is placed in a muffle furnace and heated to 250°C at a heating rate of 5°C / min and calcined for 16 hours to obtain a catalyst for catalytic oxidation of hydrogen chloride to produce chlorine.

[0062] 3) The obtained SiO2-AlN supported ruthenium catalyst was loaded into a fixed bed reactor, and a mixture of hydrogen chloride and oxygen was introduced, HCl / O2=1 / 1, the reaction pressure was 0.1MPa, the reaction temperature was 350°C, and the mass space velocity was 20h -1 Under the above conditions, the conversion rate was 70% after 50h of reaction; after 1000h of reaction, the conversion rate of hydrogen chloride was 57%.

[0063] Comparative Example 3

[0064] 1) Weigh 6 g AlN, 2 g SiO2 and 2 g Si3N4 and grind them evenly in a mortar to obtain a Si3N4-SiO2-AlN composite material carrier.

[0065] 2) Loading ruthenium by impregnation method. Take 1 ml of ruthenium chloride solution and add 10 ml of anhydrous ethanol to dissolve it, then pour 10 g of Si3N4-SiO2-AlN carrier and stir it thoroughly on a stirrer for 6 hours. Then put it in an oven and dry it at 70°C for 12 hours. The dried catalyst is placed in a muffle furnace and heated to 250°C at a heating rate of 5°C / min and calcined for 16 hours to obtain a catalyst for catalytic oxidation of hydrogen chloride to produce chlorine.

[0066] 3) The obtained Si3N4-SiO2-AlN supported ruthenium catalyst was loaded into a fixed bed reactor, and a mixture of hydrogen chloride and oxygen was introduced, HCl / O2=1 / 1, the reaction pressure was 0.1MPa, the reaction temperature was 350°C, and the mass space velocity was 20h -1 Under the above conditions, the conversion rate was 69% after 50h of reaction; after 1000h of reaction, the conversion rate of hydrogen chloride was 53%.

[0067] Comparative Example 4

[0068] 1) Weigh 6 g AlN, 1 g SiO2 and 3 g Si3N4 and grind them evenly in a mortar to obtain a Si3N4-SiO2-AlN composite material carrier.

[0069] 2) Load ruthenium by impregnation. Take 1 ml of ruthenium chloride solution and add 10 ml of anhydrous ethanol to dissolve it, then pour the Si3N4-SiO2-AlN carrier (10 g) and stir it thoroughly on a stirrer for 6 hours. Then put it in an oven and dry it at 70°C for 12 hours. The dried catalyst is placed in a muffle furnace and heated to 250°C at a heating rate of 5°C / min and calcined for 16 hours to obtain a catalyst for catalytic oxidation of hydrogen chloride to produce chlorine.

[0070] 3) The obtained Si3N4-SiO2-AlN supported ruthenium catalyst was loaded into a fixed bed reactor, and a mixture of hydrogen chloride and oxygen was introduced, HCl / O2=1 / 1, the reaction pressure was 0.1MPa, the reaction temperature was 350°C, and the mass space velocity was 20h -1 Under the above conditions, the conversion rate was 80% after 50h of reaction; after 1000h of reaction, the conversion rate of hydrogen chloride was 64%.

[0071] Comparative Example 5

[0072] 1) Weigh 6 g AlN, 3 g SiO2 and 1 g Si3N4 and grind them evenly in a mortar to obtain a Si3N4-SiO2-AlN composite material carrier.

[0073] 2) Load ruthenium by impregnation. Take 1 ml of ruthenium chloride solution and add 10 ml of anhydrous ethanol to dissolve it, then pour the Si3N4-SiO2-AlN carrier (10 g) and stir it thoroughly on a stirrer for 6 hours. Then put it in an oven and dry it at 70°C for 12 hours. The dried catalyst is placed in a muffle furnace and heated to 250°C at a heating rate of 5°C / min and calcined for 16 hours to obtain a catalyst for catalytic oxidation of hydrogen chloride to produce chlorine.

[0074] 3) The obtained Si3N4-SiO2-AlN supported ruthenium catalyst was loaded into a fixed bed reactor, and a mixture of hydrogen chloride and oxygen was introduced, HCl / O2=1 / 1, the reaction pressure was 0.1MPa, the reaction temperature was 350°C, and the mass space velocity was 20h -1 Under the above conditions, the conversion rate was 79% after 50h of reaction; after 1000h of reaction, the conversion rate of hydrogen chloride was 66%.

Claims

1. A catalyst for hydrogen chloride oxidation, characterized in that: The catalyst for hydrogen chloride oxidation is a supported ruthenium-based catalyst, and the carrier of the supported ruthenium-based catalyst is a silicon nitride-aluminum nitride composite material, a silicon dioxide-aluminum nitride composite material or a silicon dioxide-silicon nitride-aluminum nitride composite material; in the silicon nitride-aluminum nitride composite material, the mass ratio of aluminum nitride to silicon nitride is 9-7:1-3; in the silicon dioxide-aluminum nitride composite material, the mass ratio of aluminum nitride to silicon dioxide is 9-7:1-3; in the silicon dioxide-silicon nitride-aluminum nitride composite material, the mass ratio of aluminum nitride to silicon dioxide and silicon nitride is 6-8:1-3:1-3; in the silicon nitride-aluminum nitride composite material, the silicon dioxide-aluminum nitride composite material or the silicon dioxide-silicon nitride- The aluminum nitride composite material is prepared by the following method: Si3N4 and AlN, SiO2 and AlN or SiO2, Si3N4 and AlN are mixed in a certain proportion, respectively, and loaded into a ball milling jar, and anhydrous ethanol is used as a medium, and ball milling is performed at 100-300 rpm for 10-20 hours by a ball mill; the obtained ball milling product is poured into a quartz boat, and placed in the center of a heating reaction section of a tubular furnace, and heated to 400-1000° C. at a rate of 10-20° C. / min in a nitrogen atmosphere with a flow rate of 5-15 mL / min, sintered for 3-10 hours, and cooled to room temperature to obtain a silicon nitride-aluminum nitride composite material, a silicon dioxide-aluminum nitride composite material or a silicon dioxide-silicon nitride-aluminum nitride composite material; The catalyst is prepared by the following method: taking a ruthenium chloride aqueous solution and adding ethanol to dissolve it, then adding a carrier, fully stirring it on a stirrer for 3-10 hours, then putting it into an oven to dry it at 60-100°C for 6-12 hours, and after drying, putting it into a muffle furnace, heating it to 200-300°C at a heating rate of 5-10°C / min, and calcining it at this temperature for 10-20 hours to obtain a supported ruthenium-based catalyst.

2. The catalyst according to claim 1, characterized in that: The mass ratio of ruthenium in ruthenium chloride to the carrier is controlled to be 0.5-5:

100.

3. The catalyst according to claim 1 or 2, characterized in that: The aluminum nitride is prepared by the following method: aluminum powder and NH4Cl are ground and mixed evenly, so that the weight ratio of NH4Cl in the mixture is between 30% and 70%; the mixture of aluminum and NH4Cl is placed in an alumina boat, the alumina boat is placed in the center of the heating section of a tubular furnace reactor, nitrogen is supplied to the tubular furnace reactor at a flow rate of 5-10 mL / min, and it is heated to a calcination temperature at a rate of 5-15°C / min, the calcination temperature is between 500-1000°C, and calcined at the calcination temperature for 3-10 hours, and then cooled to room temperature to obtain an aluminum nitride carrier.

4. A method for preparing a catalyst for hydrogen chloride oxidation as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: 1) Prepare the carrier by the following method b: Method b: Grind and mix aluminum and NH4Cl evenly, so that the weight ratio of NH4Cl in the mixture is between 30% and 70%; put the mixture of aluminum and NH4Cl in an alumina boat, place the alumina boat in the center of the heating section of a tubular furnace reactor, supply nitrogen gas at a flow rate of 5-10mL / min to the tubular furnace reactor, heat it to a calcination temperature at a rate of 5-15℃ / min, the calcination temperature is between 500-1000℃, and calcine at the calcination temperature for 3-10 hours, then cool to room temperature to obtain AlN; Si3N4 and AlN, SiO2 and AlN or SiO2, Si3N4 and AlN are mixed in a certain proportion, respectively, and loaded into a ball milling jar, and anhydrous ethanol is used as a medium, and ball milled at 100-300 rpm for 10-20 hours; the obtained ball milling product is poured into a quartz boat, and placed in the center of a tube furnace heating reaction section, and heated to 400-1000° C. at a rate of 10-20° C. / min in a nitrogen atmosphere with a flow rate of 5-15 mL / min, and sintered for 3-10 hours, and then cooled to room temperature to obtain a silicon nitride-aluminum nitride composite material, a silicon dioxide-aluminum nitride composite material or a silicon dioxide-silicon nitride-aluminum nitride composite material carrier; 2) Take ruthenium chloride aqueous solution and add ethanol to dissolve it, then add the carrier, stir it on a stirrer for 3-10 hours, then put it into an oven and dry it at 60-100°C for 6-12 hours, put it into a muffle furnace after drying, heat it to 200-300°C at a heating rate of 5-10°C / min, and calcine it at this temperature for 10-20 hours to obtain a supported ruthenium-based catalyst.

5. The preparation method according to claim 4, characterized in that: In step 2), the temperature is raised to 250° C. at a heating rate of 5° C. / min and calcined for 16 hours.

Citation Information

Patent Citations

  • Catalyst for oxidation reactions in the presence of hydrogen chloride and / or chlorine and method the production thereof, and the use thereof

    CN102239003A

  • Process for the preparation of chlorine, bromine or iodine and for the preparation of halogenated hydrocarbons

    GB1046313A

  • Process for producing chlorine

    US5908607A

  • High-heat conductivity silicon nitride-aluminum nitride composite material and preparation method thereof

    CN105503199A

  • Preparation method of aluminum nitride powder with dense morphology

    CN109467064A